2009
DOI: 10.1002/pssc.200880577
|View full text |Cite
|
Sign up to set email alerts
|

Emission spectrum of a quantum dot embedded in a nanocavity

Abstract: We model the emission spectrum of a quantum dot embedded in a (e.g. photonic crystal) nanocavity, using a semi-classical approach to describe the matter-field interaction. We start from the simple model of a quantum dot as a two-level system, and recover the result expected from cavity quantum electrodynamics. Then, we study the influence of electron-acoustic-phonons interaction. We show that the surrounding semiconductor plays an essential role in the emission spectrum in strong coupling.Schematic of the L1 c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Figure 4(b) shows the autocorrelation histogram of the cavity emission, which indicates g ð2Þ ð0Þ ¼ 0:19ð1Þ. The clear antibunching is markedly different from previous reports which observed weak or no antibunching of the detuned PC cavity mode [2,3], and may be attributed to the expected absence of multiexciton population of the QD under resonant excitation of the single-exciton [25]. A significant contribution to the value of g ð2Þ ð0Þ is due to overlap of the 40-ps pulses with the filter at the cavity frequency, which could be improved by a narrower filter or larger QD-cavity detuning.…”
mentioning
confidence: 71%
“…Figure 4(b) shows the autocorrelation histogram of the cavity emission, which indicates g ð2Þ ð0Þ ¼ 0:19ð1Þ. The clear antibunching is markedly different from previous reports which observed weak or no antibunching of the detuned PC cavity mode [2,3], and may be attributed to the expected absence of multiexciton population of the QD under resonant excitation of the single-exciton [25]. A significant contribution to the value of g ð2Þ ð0Þ is due to overlap of the 40-ps pulses with the filter at the cavity frequency, which could be improved by a narrower filter or larger QD-cavity detuning.…”
mentioning
confidence: 71%
“…As for cavity-QED, theoretical work has suggested that such pure phonon dephasing might be responsible for cavity feeding at detunings of the order of the polariton linewidths. 25,26,27,28,29 Experimental work has confirmed that for such small detunings dephasing plays a crucial role.…”
mentioning
confidence: 90%
“…This behaviour is indicative of a complex light-matter interaction in a semiconductor well beyond the widely used two-level emitter-cavity schemes. Different mechanisms such as photon-induced 'shake-up' processes in charged quantum dots [6], dephasing processes [7,8,9] and phonon-mediated processes [10] are currently discussed to understand the experimentally observed features. A well prepared and clearly defined experimental situation is therefore mandatory to gain a thorough understanding of the responsible physical mechanisms behind the non-resonant dot-cavity coupling.Here we present experimental investigations on the non-resonant dot-cavity coupling of a single quantum dot inside a micro-pillar where the dot has been resonantly excited in the s-shell, thereby avoiding the generation of additional charges in the QD and its surrounding.…”
mentioning
confidence: 99%
“…This so-called non-resonantly coupled emission mechanism is not well understood and controversially discussed in the literature: Kaniber et al [6] suggested that the experimentally observed coupling between a single QD and a photonic crystal cavity mode is mediated by photon-induced 'shake-up'-like processes in charged quantum dots. In their theoretical work [7,9], Naesby et al and Auffèves et al demonstrated that dephasing shifts the emission intensity towards the cavity frequency, whereas Tarel and Savona [10] showed the important role of the electron-acoustic-phonon interaction for understanding the emission properties. From the experimental point of view it is desirable to study the coupling mechanism via purely resonant excitation of the QD s-shell in order to obtain a better understanding of the underlying physics.…”
mentioning
confidence: 99%